Lack of educational impact of video game addiction in children and adolescents diagnosed with ADHD: A cross-sectional study - Blasco-Fontecilla, Hilario; Menéndez-García, Ángela; Sanchez-Sanchez, Fernando; Bella-Fernández, Marcos (Frontiers in Psychiatry, 2023)
The use of video games has become widespread worldwide. Excessive use of videogames is increasingly becoming a matter of concern, particularly in patients diagnosed with attention deficit hyperactivity disorder (ADHD). Currently, international gaming disorder (IGD) is not included within the DSM-5-chapter Disorders related to substances and addictive disorders. This is a post-hoc descriptive naturalistic study comparing children and adolescents diagnosed with ADHD with and without IGD. We used the 85% cut-off point of the ADITEC-V to split our sample of ADHD patients into those with IGD (>85%), and those without IGD (<85%). 13 (25%) out of the 51 ADHD children and adolescents included in our study had an IGD. Patients with IGD had a first contact with internet, mobiles and videogames at a very early age (5.67 ± 3.31, 6.33 ± 4.60, and 7.50 ± 2.61, respectively). However, only age at first contact with internet was statistically significant different when comparing ADHD patients with and without IGD (8.68 ± 2.71 vs. 5.67 ± 3.31, t=3.166, df=47, p=0.01). Different neurodevelopmental, clinical, and neuropsychological measures converged in that impulsivity is a risk factor for IGD. Unexpectedly, we found no association between IGD and poor academic achievement. Future studies may include randomized controlled trials for treating IGD, the study of social adjustment as a protective factor against developing an IGD, and the role of serious and non-serious video games in the development of an IGD, among others. Additional research is clearly needed on IGD.